Pengaruh pemahaman perpajakan dan sanksi perpajakan terhadap kepatuhan wajib pajak UMKM di Kota Maumere - Ignas Pau, Hilarius; Nawa Pau, Sarlin P. Nawa Pau; F. Angi, Yohana (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2022)
This study aims to determine the effect of Tax Understanding and Tax Sanctions on MSME Taxpayer Compliance in Maumere City. The number of research samples was 100 MSME actors obtained using the Slovin formula and the technique used was simple random sampling. The analysis technique used in this research is multiple linear regression analysis, classical assumption test consisting of Normality test, Multicollinearity test, Heteroscedasticity test and Hypothesis test consisting of t test, F test and Coefficient of Determination test. The results of the analysis show that understanding of taxation has an effect on taxpayer compliance. This shows that the higher the understanding of taxation, the higher the taxpayer compliance. Tax sanctions have no effect on taxpayer compliance. It can be concluded that the higher the tax sanction, the lower the taxpayer compliance.